Evaluation of Corrosion Potential Stability of Stainless Steels in Dilute Electrolyte Solution for Application to a Quasi-Reference Electrode Used in Electrochemical Sensing System - Kyosuke Sawada; Shinji Okazaki; Tatsuki Inaba; Motohiro Sakuma; Koichi Azuma (Chemosensors)
To evaluate the long term corrosion potential stability of stainless steel (SS) in environmental water, the corrosion potential of SUS304, SUS316, SUS316L, and SUS430 was measured for 1 week in a solution of 0.9 mM NaHCO3 and 0.5 mM CaCl2, referred to as “sub-tap water.” The potential of the SSs upon initial immersion in sub-tap water was approximately 10 times less stable than the potentials of Fe and Cu. However, as immersion continued, the stability of the corrosion potential of the SS improved and became equivalent to those of Fe and Cu. The stability could be manipulated by pretreatment (pre-immersion) before samples were immersed in sub-tap water. The stability was increased by pre-immersion in an acidic solution but was reduced by a passivation treatment. The formation of iron oxides on the SS surface stabilized the potential, whereas surface enrichment with Cr led to instability. This behavior can also be inferred from a comparison of the polarization curves, where the passive current after the passivation treatment was the largest. This result is also speculatively attributed to the corrosion potential in sub-tap water decreasing over time after the passivation treatment. The charge transfer resistance likely contributes significantly to the potential stability, as indicated by an equivalent circuit analysis based on electrochemical impedance spectroscopy. The results showed that, when stabilizing the corrosion potential of SS, there is no need to reduce the charge transfer resistance as with existing reference electrodes. Stability is achieved when the surface thickness is such that the pseudo-capacitance in a dilute solution is less than 10 µF sα−1cm−2 and potential stability does not influence a few changes in the CPE1 value after potential stability is achieved. The results of this study show that SS can be used as a quasi-reference electrode material. We expect the findings presented herein to strongly affect the development of electrochemical sensors that can be easily used in long term continuous measurements and in situ applications.